Empirical Inference with Equilibrium Search Models of the Labor Market - Gerard J. van den Berg (Tinbergen Institute, 1998)
This paper examines the use of equilibrium search models in the empiricalanalysis of labor markets. We survey the literature on structural estimationof these models with micro data on wages and durations, and we discuss theadvantages of the equilibrium approach, for policy analysis and forunderstanding a number of stylized facts that are hard to explain otherwise.During the past years, substantial progress has been made in terms of theexplanatory power of these models. We finish with a critical examination ofthe extent to which the approach can be fruitfully applied to (matchedworker-)firm data.
Keywords: 330; Arbeitsuche; Arbeitsmarkt; Gleichgewichtstheorie; Theorie